Diel variation in the structure of fish assemblages in south western Amazon streams - Igor David da Costa; Wesclen Vilar Nogueira (Acta Limnologica Brasiliensia)
Abstract: Aim We investigate the influence of luminosity, habitat conservation and pluviometric periods in fish assemblages of in pasture and forest small streams in western amazon. Methods Sampling was conducted every two months from July 2013 to April 2014 in nine first- and second-order streams using seine nets and dip nets during the day and night. Fish composition, richness and total abundance were determined for each sampling period. The PERMANOVA was used to evaluate the effects of land use, season, and photoperiod, on fish assemblages. Fish assemblage structure for each stream in the presence and absence of photoperiod was ordered by NMDS analysis. Results In the light period, 3,484 specimens from 69 species were collected, while 4,574 specimens from 71 species where collected in the dark period. No significant differences in abundance and species richness were recorded between the presence and absence of luminosity periods, rainy and dry seasons and streams in forest and deforested areas. We found evidence of the dark phase composition and richness of exclusive species (22% of species collected were found at night), which were greater than in the light period (20% of species). Conclusion Despite our failure to identify any nycterohemeral segregation, the results complement existing knowledge of regional ichthyofauna and help provide a better understanding of the distributional, behavioral and functional ecological patterns of fish assemblages.